Fast chlorophyll fluorescence transients as selection tools for submergence tolerance in rice (Oryza sativa) - Pandey, Debabrata; Sharma, S G; Sarkar, R K (The Indian Journal of Agricultural Sciences, 2008)
An experiment was conducted during 2005-06 with 20 Indica rice (Oryza sativa L.) cultivars to study the feasibility of employing chlorophyll fluorescence as a selection tool for submergence tolerance in rice. Fourteen-days-old seedlings were completely submerged for 2, 4, 6, 8 and 10 days. Chlorophyll a fluorescence was recorded at a regular interval of 2 days up to the day 8 in fully dark-adapted detached leaves after subjecting the plants to 1 hr of re-emergence. Quantification and de-convolution of the chlorophyll fluorescence transients into several biophysical parameters that are indicative of photosystem II activity revealed that cultivars differed significantly in their response to submergence. The values of the efficiency with which the trapped excitons move an electron further than QA- and the probability that an absorbed photon will move an electron into electron transport chain measured under complete submergence either increased significantly or remained unchanged as in control plants. The increase was more pronounced in tolerant cultivars compared to the susceptible ones. On the other hand, the values of effective antennae size decreased under complete submergence till 6 days of submergence and increased later. The differences were either significant or nonisignificant; the magnitude of decrease in effective antennae size being greater in tolerant cultivars compared to the susceptible ones. The values of effective antennae size showed highly significant negative correlation with survival percentage, whereas the efficiency with which the trapped excitations move an electron further than QA- and the probability that an absorbed photon will move an electron into electron transport chain showed highly significant positive correlation with survival percentage. These parameters might provide bases to rank the cultivars according to their sensitivity to complete submergence.